The Effect of Storage Environment on Dimensional Changes of Acrylic Resin Post Patterns - Abbas Fallahtafti; Mohamad Hossein Lotfikamran; Seyyed Mohammad Abrisham; Reza Fallahtafti; Mojtaba Amini; Mohammad Reza Hakimi Meibodi (Mashhad University of Medical Sciences, 2018)
Introduction: The purpose of this study was to compare dimensional changes of two types of auto polymerizing acrylic resin patterns (APARPs) in three different storing environments. Methods: 60 acrylic post and core patterns were made of two types of Duralay acrylic resins (Aria dent, Iran and Reliance, Dental Mfg. Co, USA) using a canine model. Then coronal, apical diameter and coronoapical length of patterns were measured. Afterwards, they were divided into two categories of 30 for each type of Duralay acrylic resin type. Each category was divided into three groups of ten randomly to immerse in three storage environments (Deconex®53plus Borer ChemieAG, Switzerland), Unident ® Impre(USF Healthcare S.A, Sweitzerland) and water. After one hour, three mentioned values were measured again. Data were analyzed by SPSS20 using t-test, paired t-test and ANOVA. Results: Results showed that there were no statistically difference (p value> 0.05) about all dimensions of auto polymerizing acrylic post and core patterns except apical diameter and coronoapical length of Dental Mfg. Co, USA in Deconex®53 plus. Conclusion: The best environment to store Duralay APARPs with minimal changes was water and for disinfection, Deconex®53plus and Unident ® Imprecan showed acceptable properties with both of Duralay types.